STRATEGIC MANAGEMENT IN EDUCATION CONTEXT: SCIENCE MAPPING OF PRESENT AND FUTURE TRENDS - Jaafar, Farah Wahida; Ahmad, Mohd Hanafiah; Osman, Azim Azuan (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2026)
This study evaluates the knowledge structure of studies on strategic management practices in the education context. Strategic management practices are one of the key elements that can enhance educational effectiveness. It is a major contribution to landscaping schools, including innovations and a creative environment. However, there has been little comprehensive understanding of knowledge structure in strategic management practices among principals in cultivating educational effectiveness in their institutions, which is lacking in the literature. Through a bibliometric approach, 472 publications on strategic management practices were retrieved from Scopus. A bibliographic coupling and co-word analysis were performed to uncover past and predict future trends in this regard. The analysis yields noteworthy themes concerning organizational leadership and innovation, data-driven decision-making, human capital development, and stakeholder engagement. This emphasizes their influence on fostering effective strategic management practices in the education context. Additionally, the study identifies emerging trends and gaps in the current literature, offering insights into future research directions. The findings suggest that adopting a strategic combination of keywords derived from the analysis can effectively foster strategic activities, drive strategic innovation, and support strategic, sustainable academic development. Overall, this study provides a foundational framework for educational policymakers and school leaders seeking to foster vibrant strategic management practices in the school environment. This ultimately advances educational practices and outcomes.